Fintech Innovation in the Financial Sector: Influence of E-money Products on a Growing Economy - Omodero, Cordelia Onyinyechi (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
The FinTech innovation of e-money products in the financial sector has not gained sufficient recognition in Nigeria's developing country. Despite the numerous economic benefits associated with this innovation, physical cash for financial transactions is still prevalent. Banks are still experiencing some level of cash withdrawals and deposits by individuals who refuse to embrace modern technology. This study stresses the economic benefits of e-payment channels available today and statistically supports evidence to substantiate their usefulness. In this study, we use banks’ e-money products as the independent variables, while GDP is employed as a proxy for the economy. The data are collected from 2006-2019 and are analyzed with multiple regression techniques using E-views version 9 software. The result shows that all banks’ e-money products have a significant favorable influence on the economy except the POS that is yet to gain momentum. The study suggests the full implementation of the cashless policy, proper education of the populace and guidelines to check electronic fraud.